History, literature, and identity : four centuries of Sikh tradition - Grewal, J. S. (Oxford University Press, 2011)
This book examines the entire range of Sikh sacred literature produced between the sixteenth- and nineteenth century to give a comprehensive account of the Sikh tradition. Divided into five parts, it discusses the historical context of the production of Sikh literature and also the development of Sikh identity. The first part of the book (1500-1605) explores the compositions of the first five Gurus and the next analyses the literary genre characterizing the 'phase of confrontation' with the state (1606-75). The third (1675-1708) reveals how Sikhism responded to the external threats and the fourth part (1765-1849) discusses Guru Gobind Singh and literature produced during the period of Khalsa Raj. The last deals with works which have gained entry into the Sikh panth during the colonial period.